Adaptively programmable metasurface for intelligent wireless communications in complex environments - Han Qing Yang; Jun Yan Dai; Hui Dong Li; Lijie Wu; Zi Hang Shen; Qun Yan Zhou; Meng Zhen Zhang; Si Ran Wang; Zheng Xing Wang; Jun Wei Wu; Shi Jin; Wankai Tang; et al. (Nature Communications)
Abstract The programmable metasurface or reconfigurable intelligent surface is one of the emerging technologies for next-generation wireless communications, but the existing programmable metasurfaces still rely on human control to reshape the electromagnetic (EM) environment as desired. Here, we propose an adaptively programmable metasurface (APM), which integrates the capabilities of acquiring wireless environment information and manipulating the EM waves in programmable manners. APM can sense the complex EM field distributions around and dynamically manipulate the EM waves and signals in real time under the guidance of the sensed information, eliminating the need for prior knowledge or external input on the wireless environment. For experimental verification, a 6 × 6 APM prototype is constructed and its dual capabilities of sensing and wave manipulation are validated. Different integrated sensing and communication scenarios with and without the aid of APM are established, and the capability of APM in enhancing the communication quality is demonstrated in complex environments, highlighting its beneficial application potentials in future wireless systems.